GARAPAN ADMINISTRASI DAN MANAJEMEN PESANTREN: MENUJU PENDIDIKAN ISLAM YANG BERKUALITAS - Fadhilah, Farras; Amiruddin; Saila Rahma Annisa Nasution; Eka Satya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore strategies for improving the quality of education in Islamic boarding schools through optimizing administration and management. The method used is literature study, by analyzing various relevant literature. The research results show that Islamic boarding school administration and management includes operational management, leadership, human resource management, curriculum development, and relations with the community. Islamic boarding school management models are divided into three: the traditional model which emphasizes religious values, the modern model which adopts a contemporary management approach, and the hybrid model which combines the two models. The success of Islamic boarding school management is determined by several key factors: visionary leadership, participation and collaboration of all Islamic boarding school components, availability of adequate infrastructure, sustainable evaluation and monitoring systems, as well as external support from the government and other institutions. The main recommendations include developing leadership capacity through training, improving the quality of teaching staff, curriculum innovation, increasing parent and community involvement, and strengthening information and technology systems. By implementing these recommendations, Islamic boarding schools are expected to improve the quality of education and produce graduates who have a deep religious understanding and skills that are relevant to the needs of the times. This research offers a solid theoretical foundation and practical guidance for Islamic boarding school management to achieve higher education goals.